Pengembangan Media Pembelajaran Berbasis Kontekstual Berbantuan Articulate Storyline pada Materi Barisan dan Deret Geometri - Maulidar, Nurul; Syamsuddin, Nuralam; Khairina, Khairina (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
This research is based on the low interest and understanding of students in the material on sequences and series, as well as the limited use of interactive learning media that can present real contexts in the learning process. The purpose of this study was to observe the process and results of developing contextual learning media based on Articulate Storyline on the material of geometric sequences and series. This research is a development research with an approach to Thiagarajan's 4D development model which consists of four stages, namely Define, Design, Develop, and Disseminate. The subjects of this research trial were teachers and students of class X of SMA Negeri 5 Banda Aceh. Data was collected through validation sheets, teacher and student practicality sheets. The results of the validation analysis from experts show that the media obtained a validation score of 82.86% which is included in the very valid category, and the validation results by material experts were 75.76% which is included in the valid category. Based on the teacher's practicality sheet, the results obtained were 80.36% (Very Practical) and the results of the validation of the student's practicality sheet that was tested were 81.20% (Very Practical). Based on the overall results of the process of developing contextual learning media on the material of sequences and series assisted by Articulate Storyline, it is stated that it is valid and practical for use in learning activities.